Development of fish scale-collagen cream (CoC) from water-in-virgin coconut oil emulsion medium for topical application - Hasnor Izzati Che Razali (Tanjong Malim, 2019)
Development of fish scale-collagen cream (CoC) from water-in-virgin coconut oil emulsion medium for topical application by Hasnor Izzati Che Razali